Facilitating participation in conversation groups for aphasia. Issue 6 (3rd June 2021) - Archer, Brent; Azios, Jamie H.; Gulick, Nora; Tetnowski, Jennifer
ABSTRACT: Background: Although facilitated group conversations for aphasia are a popular practice within contemporary clinical aphasiology, only a small number of published studies have shed some light on how interaction occurs in this setting. One aspect of aphasia group conversation that has been mentioned in the literature but that has not yet been the focus of intensive study is participation management. Facilitators report that finding ways to help people with verbal language impairments participate in conversation is one of the central challenges faced by the clinicians and volunteers who lead these groups. However, thus far, no in-depth, interactionally-oriented research on how facilitators support group members with limited expressive language abilities exists. Aims: The aim of this study was to investigate how facilitators support people with non-fluent aphasia during group conversation. Method/procedures: We applied conversation analysis (CA) to nine video recordings of conversation groups involving people with aphasia. These videos were recorded at three sites in North America (three sites X three recordings). Each of the sessions we analysed were facilitated by experienced facilitators: Catina at Site 1, Cooper at Site 2 and Lyra at Site 3. Results/outcomes: Our analysis revealed that facilitators and group members constructed two types of sequences that supported participation by people with non-fluent aphasia (PwNFA) namely floor transfers and question-answer series. Floor transfers established a shared group focus on a specific PwNFA while question-answer series furnished PwNFA opportunities to contribute several relevant, consecutive turns to the conversation. Conclusions: The sequences we identified appeared to be designed to promote meaningful conversational participation by group members with verbal output difficulties. The behaviours that facilitators and group members engage in during these sessions could plausibly be used in other settings and suggest foci for future studies of aphasia groups.